Effect of Mozart Classical Music Therapy on Dysmenorrhea in Female Adolescents at SMA Negeri 3 Palangka Raya - Novitasari, Jessika; Mawaddah, Sofia; Noordiati, Noordiati (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Dysmenorrhea is defined as painful menstrual cramps caused by progesterone hormone imbalance and uterine contractions. The higher the prostaglandin level, the stronger the contractions and the more intense the pain. Menstruation is a regular monthly occurrence for women during their reproductive years, except during pregnancy. One of the therapies to reduce dysmenorrhea is Mozart classical music therapy, which stimulates endorphin production and provides a relaxation effect.This study aims to examine the effect of Mozart classical music therapy on dysmenorrhea in female students at SMA Negeri 3 Palangka Raya. The research design was a pre-experimental study with a pretest-posttest approach. The sample consisted of 100 female students aged 18-24 who experienced dysmenorrhea, selected through simple random sampling. The intervention protocol involved administering Mozart classical music therapy for 30 minutes daily over a period of one week. Data collection points included a pretest conducted on the first day of the intervention and a posttest on the eighth day. Data were analyzed using univariate and bivariate analysis with the Wilcoxon test. The results indicated a significant reduction in menstrual pain following the music therapy, with z-values of 5.00 to 8.00 for the pretest and 0.00 to 2.00 for the posttest, and a p-value of 0.000 (p < 0.05). Mozart classical music therapy significantly reduces dysmenorrhea in female adolescents at SMA Negeri 3 Palangka Raya, suggesting its potential as a non-pharmacological treatment option